Pengaruh Kualitas Layanan dan Kepuasan Terhadap Loyalitas Pengunjung Malang Town Square - Nur Hidayatri; Yulis Nurul Aini; Sanita Dzakirah (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The retail industry in Indonesia continues to grow along with increasing consumer expectations and competition between shopping centers. This study aims to determine the effect of service quality and satisfaction on visitor loyalty Malang Town Square (Matos).The method used is a quantitative approach with a purposive sampling technique of 96 respondents.The data was analyzed using multiple linear regression with the help of SPSS. The results showed that service quality and satisfaction had a significant effect on loyalty simultaneously and partially. Service quality has a more dominant influence than satisfaction. The conclusion of this study shows that improving service quality and satisfaction is an important strategy in building visitor loyalty in the midst of intense competition.